Peran beauty influencer terhadap perilaku impulsive buying produk kecantikan - Putri, Wulan Cahyaning; Asyraf, M. Fahmi Aufar (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2025)
Technological advances encourage the development of digital marketing, including the use of beauty influencers in promoting beauty products. This phenomenon then led to impulse buying behavior in consumers of beauty products. This study aims to determine the effect of beauty influencers on impulse buying behavior on beauty products. Respondents in this study were 114 social media users who follow beauty influencers and have purchased products reviewed by beauty influencers. Data were collected through questionnaires distributed through social media. The scale used in this study is the Impulse Buying Tendency Scale from Verplanken and Herabadi (2001). The data analysis technique used spearman rank correlation with the help of the SPSS version 23 program. The results showed that the two variables had a significant relationship with a significance value of 0.004 < 0.05. Meanwhile, the relationship between the two variables has a fairly strong relationship with a correlation coefficient value of 0.271. This finding indicates that the higher the influence of influencers, the higher the impulse buying behavior on beauty products